Current Advances and Future Perspectives of Advanced Polymer Processing for Bone and Tissue Engineering: Morphological Control and Applications - Zhang, Tongrui; Nie, Min; Li, Yijun (Frontiers in Bioengineering and Biotechnology, 2022)
Advanced polymer processing has received extensive attention due to its unique control of complex force fields and its customizability, and has been widely applied in various fields. Functional devices produced by advanced polymer processing represent an important direction in the development of next-generation manufacturing and present promising applications in biomedical engineering and other fields. However, the expensive equipment cost and lack of universality of materials also limit the development of advanced processing technologies. This review aims to provide an overview of various advanced processing techniques including micro extrusion, micro injection molding, 3D printing and their recent progresses in the field of cell proliferation, bone repair, and artificial blood vessels . This paper attempts to provide a comprehensive prospect of the challenges and opportunities for various advanced processing technologies in the field of biomedical engineering, and also aims to inspire future research directions in the field of advanced polymer processing.